Chinese Grammar Learning through Small Group Discussion: A Study on Comprehensive Chinese Courses at UNNES - Dian Yuni Pamuji; Clarosa Amanda Hasel; Ruth Kiana Nuratri (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2026)
This study aims to describe the implementation of the Small Group Discussion method in grammar learning within comprehensive courses, namely Gaoji Hanyu Zonghe (Advanced Comprehensive Chinese) for the Class of 2022 and Zhongji Hanyu Zonghe Shang (Intermediate Comprehensive Chinese I) for the Class of 2023 in the Chinese Language Education Study Program. The study employed a qualitative descriptive method, with data collection comprising observation, interviews, and documentation. Interviews were conducted with students to elicit their responses and to identify the advantages and disadvantages of the group discussion method in Chinese grammar learning. The results showed that the discussion method was successfully implemented in Gaoji Hanyu Zonghe (Advanced Comprehensive Chinese) for the Class of 2022, as students were active and responsive throughout the learning process. Small Group Discussion helped students study grammar before class, improved their critical thinking and public speaking skills, and created a more interactive learning environment. In addition, peer tutoring enabled students to understand the material more easily. In contrast, in Zhongji Hanyu Zonghe Shang (Intermediate Comprehensive Chinese I) for the Class of 2023, the Small Group Discussion method did not show significant results because students tended to be passive and lacked a strong grammar foundation. The identified obstacles included limited contributions from group members, misunderstandings of grammar, and reliance on AI to understand the material. This study concludes that the success of the discussion method is influenced by students' activity, readiness in basic grammar, and the lecturer's guidance during the learning process.